Is the typical stage of Penicillus capitatus Lamarck (Bryopsidales, Halimedaceae) a possible indicator of climate warming? - PAGANA, ILARIA; PUGLIA, GIUSEPPE DIEGO; MARLETTA, GIULIANA; ALONGI, GIUSEPPINA (Mediterranean Marine Science, 2024)
In this study, through morphological and molecular analysis approaches, we documented the presence of the typical stage (adult stage) of Penicillus capitatus during the coldest seasons of the year, typically periods when this form had never been reported in the Mediterranean. Indeed, the typical stage is common throughout the year in the western Atlantic (native range of the species), whereas it is rare in the Mediterranean, where the Espera stage (juvenile stage) is the main stage. To date, in the Mediterranean, the adult stage has been found only in the warmer months of the year. Therefore, the observation of the typical stage in the Mediterranean Sea during the cold season might suggest a general increase in the seawater temperature in this basin, rendering this stage of P. capitatus a potential climate bioindicator. Furthermore, owing to the molecular analysis methods adopted, it was possible to assess the relationships between the Mediterranean and Atlantic populations of this species.